Mechanisms Modified by (−)-Epicatechin and Taxifolin Relevant for the Treatment of Hypertension and Viral Infection: Knowledge from Preclinical Studies - Iveta Bernatova; Silvia Liskova (MDPI AG, 2021)
Various studies have shown that certain flavonoids, flavonoid-containing plant extracts, and foods can improve human health. Experimental studies showed that flavonoids have the capacity to alter physiological processes as well as cellular and molecular mechanisms associated with their antioxidant properties. An important function of flavonoids was determined in the cardiovascular system, namely their capacity to lower blood pressure and to improve endothelial function. (−)-Epicatechin and taxifolin are two flavonoids with notable antihypertensive effects and multiple beneficial actions in the cardiovascular system, but they also possess antiviral effects, which may be of particular importance in the ongoing pandemic situation. Thus, this review is focused on the current knowledge of (−)-epicatechin as well as (+)-taxifolin and/or (−)-taxifolin-modified biological action and underlining molecular mechanisms determined in preclinical studies, which are relevant not only to the treatment of hypertension per se but may provide additional antiviral benefits that could be relevant to the treatment of hypertensive subjects with SARS-CoV-2 infection.